Configuration analysis of negative silence in college classroom based on FSQCA method - Jian Chen; Baozhong Ye; Haifeng Miao (Scientific Reports)
Abstract Currently, negative silence among students in college classroom is quite common. However, existing research on this phenomenon tends to analyze the net effects of antecedent conditions on outcome. In fact, negative silence in college classroom is the result of multiple factors working together. Therefore, this paper takes 222 college students as research samples and uses FSQCA method to analyze the relationships between five antecedent conditions (self-efficacy, fear of negative evaluation, interest, verbal immediacy, and nonverbal immediacy) and negative classroom silence from the configuration perspective. The results indicate that none of these conditions is necessary for the negative silence. On the contrary, three configurations of conditions could lead to this issue. The first configuration contains self-efficacy, fear of negative evaluation, and verbal immediacy. The second configuration includes self-efficacy, fear of negative evaluation, and nonverbal immediacy. The third configuration consists of self-efficacy, interest, verbal immediacy, and nonverbal immediacy. The research results of this article reveal the related factors and their configurations of negative silence in college classroom, which can help to gain a comprehensive understanding of the reasons for the phenomenon and provide references for breaking it. For instance, in teaching and learning process, it is necessary to use methods such as encouragement and appreciation to promote the self-efficacy of college students, provide effective guidance for college students to overcome the fear of negative evaluation, combine more real-life examples with knowledge to enhance college students’ learning interest, and use more verbal and nonverbal immediacy behaviors to attract the attention of college students in the classroom, so as to achieve an active and effective learning atmosphere.